The attenuation of myocardial hypertrophy by atorvastatin via the intracellular calcium signal and the p38 MAPK pathway - Yang, Chuang (Int J Clin Exp Pathol, 2019)
Objective: It is well documented that atorvastatin could protect against atherosclerosis, cardiac fibrosis, etc. However, few reports have drawn the link between atorvastatin and myocardial hypertrophy, a common type of myocardial damage. This study aimed to illustrate the effects of atorvastatin on Ang II-induced cardiac hypertrophy and to reveal its mechanism. Methods: We established cardiac hypertrophy by exposing cardiomyocytes to Ang II. Then we determined whether atorvastatin could reverse cardiac hypertrophy markers and several cellular responses induced by Ang II to normal levels. Finally, we tried to illustrate the mechanism of these effects. Results: Atorvastatin performed very well in resuming cardiac hypertrophy. It could attenuate the increase of oxidative stress and cell apoptosis in cardiomyocyte cells. The activation of the p38 MAPK signaling pathway induced by Ang II was well inhibited by atorvastatin. Additionally, the Ca(2+) concentration in cells and the calcineurin (CaN) expression level were also significantly mitigated by atorvastatin. Conclusion: Atorvastatin can attenuate cardiac hypertrophy induced by Ang II via the intracellular calcium signal and the p38 MAPK pathway. It provides a therapeutic potential for the treatment of myocardial hypertrophy.